Analysis of the Correlation between the Distribution of MTHFR Gene and the Severity and Renal Function of Elderly Patients with H-Type Hypertension. (12th April 2022) - Zhang, Chi; Dou, Zhijie; Zhao, Cui; Li, Jun; Xin, Qiuping; Feng, Yumei; Xie, Yunbo; Cao, Junjie
Abstract : In order to investigate the correlation between the distribution of methylenetetrahydrofolate reductase (MTHFR, MR) C677T gene and the severity of disease and renal function in elderly patients with H-type hypertension, a total of 170 patients with H-type hypertension admitted to our hospital from September 2020 to February 2021 and 173 elderly patients with non-H-type hypertension during the same period are selected as the research objects and are respectively included in the observation group and control group. Baseline data and distribution of MR C677T genotype are compared between the two groups, influencing factors of H-type hypertension are analyzed by logistic regression analysis, and differences and correlation of homocysteine (Hcy) and estimated glomerular filtration rate (eGFR) levels in different MR C677T genotypes are compared. The influence of MR C677T genotype on the severity and renal function of patients with H-type hypertension is further analyzed. There are many influencing factors for H-type hypertension, including advanced age, high-sodium diet, and MR TT genotype. Patients with hypertension with these risk factors should be monitored. H-type hypertension has a high frequency of carrying TT genotype and T allele, and the TT genotype in H-type hypertension will affect the Hcy and eGFR levels. Therefore, Hcy level of H-type hypertension patients with TT genotype should be actively controlled to help control the disease and reduce kidney damage. MR TT genotype can be used as a reference index in the early screening of H-type hypertension.